IMPLEMENTATION OF AUGMENTED REALITY IN THE INTRODUCTION OF CAKES USING SURF ALGORITHM IN CILLA SNACK - Jannah Nurlillah; Dadang Hamdani; Yati Nurhayati (Balong International Journal of Design, 2019)
ABSTRACTThe role of the media is quite important in providing information about cakes stock in Cilla Snack, to the wider community. The delivery of information is usually done in the form of brochures. But brochures are considered inadequate in providing visualization about the cake and not all cake information can be included in the brochure that make consumers do not get complete information. Augmented Reality Technology, is the right technology to provide cake information on Cilla Snack. The implementation of Augmented Reality technology on android smartphones using the SURF (Speeded Up Robust Features) algorithm, this algorithm can recognize images with good recognition speed. In the development of AR applications that use the SURF algorithm, there are 3 stages, namely initialization, tracking markers, and object rendering. At the initialization stage, the image used as the introduction database will be processed. At the tracking marker stage, the smartphone camera will take a picture and process each input image then matching process with the image in the database. The last step is after a match is found, the application will display information text along with the cake object that matches the results of the match. Application development uses C # programming language, known as one of the object-oriented programming languages, so it is considered suitable for developing this application. With this application, brochures can provide visualization of cakes in the form of 3-dimensional objects making it more interesting and interactive than ordinary brochures. Keywords: Augmented Reality, SURF Algorithm, 3D Objects, Android.